Review of actions against labour trafficking in Finland - Jokinen, Anniina (Publication series, 2023)
Labour trafficking and exploitation of migrant workers is a widespread social problem in which vulnerable migrant workers are exploited for economic gain. Migrant workers are exploited by means of underpayment and they work long hours in poor conditions. The workers may also be threatened and controlled. In Finland, the phenomenon was identified already in the early 2000s, and over the years, anti-trafficking activities have improved and become established as part of the activities of various authorities and other parties.